2011
DOI: 10.1111/j.1540-4781.2011.01231.x
|View full text |Cite
|
Sign up to set email alerts
|

Goal Setting and Student Achievement: A Longitudinal Study

Abstract: The connection between goals and student motivation has been widely investigated in the research literature, but the relationship of goal setting and student achievement at the classroom level has remained largely unexplored. This article reports the findings of a 5‐year quasi‐experimental study examining goal setting and student achievement in the high school Spanish language classroom. The implementation of LinguaFolio, a portfolio that focuses on student self‐assessment, goal setting, and collection of evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 38 publications
5
86
0
2
Order By: Relevance
“…This study, coupled with the Moeller et al () goal‐setting study, supports the idea that the LinguaFolio accomplishes its pedagogical purpose. As with all correlative studies, it is impossible to show causality between LinguaFolio use and the positive outcomes presented.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This study, coupled with the Moeller et al () goal‐setting study, supports the idea that the LinguaFolio accomplishes its pedagogical purpose. As with all correlative studies, it is impossible to show causality between LinguaFolio use and the positive outcomes presented.…”
Section: Resultssupporting
confidence: 76%
“…Using the LinguaFolio as an intervention, Moeller, Theiler, and Wu () conducted a longitudinal study analyzing the relationship between goal setting and student achievement across time at both the individual student and instructor levels. A correlational analysis of the goal‐setting process and language proficiency scores revealed a statistically significant relationship between the goal‐setting process and language achievement ( p < 0.01).…”
Section: Fostering Srl Through Student‐centered Classroomsmentioning
confidence: 99%
“…Ryan and Cassidy () specifically suggested that internship programs require students to write a plan that identifies learning objectives and assessment strategies and to maintain a self‐reflective journal that promotes critical thinking throughout the internship period. Interventions that combine elements of goal‐setting, self‐assessment, and self‐reflection have been proven to be beneficial in promoting self‐regulated and autonomous learning (Moeller et al, ; Ziegler & Moeller, ). For instance, the description, examination, and articulation of learning (DEAL) model (Ash & Clayton, , ) employed in Bettencourt () was found to be effective in guiding learners of Spanish to reflect on their CSL experience and to take action for future improvement.…”
Section: Review Of Literaturementioning
confidence: 99%
“…What do we know from empirical research? Research at the classroom level has revealed that goalsetting, which is at the heart of Can-Do learning, promotes self-regulated learning, increases language and academic achievement, enhances motivation and task value, and improves self-assessment when it is implemented regularly and frequently (Ciesielkiewicz & Coca, 2013;Little, 2003Little, , 2009Little, Goullier, & Hughes, 2011;Moeller, Theiler, & Wu, 2012;Romjue, 2016;Ziegler, 2014;Ziegler & Moeller, 2012).…”
Section: The Science and Art Of Can-do Learningmentioning
confidence: 99%